Aspectos farmacológicos e toxicológicos do uso off-label da tadalafila na atividade física - Conceição, Sofia Moraes da (My University, 2025)
Tadalafil is a selective phosphodiesterase type 5 (PDE5) inhibitor indicated for the treatment of erectile dysfunction and pulmonary arterial hypertension. Due to its vasodilatory action, it has attracted interest in the sports field for its possible ergogenic effect. However, there is a scarcity of literature on the physiological mechanisms involved in the use of this substance and its impact on physical performance. This study, through a literature review, analyzed the pharmacological and toxicological aspects of this combination. The bibliographic search was conducted in the United States National Library of Medicine (PubMed) database, using Mesh Terms as Boolean terms in English: "(Tadalafil) AND (physical activity OR exercise OR sports performance)". After applying the exclusion criteria, nine articles were selected. The results indicated that, in healthy individuals and athletes, tadalafil did not promote significant improvements in oxygen consumption, muscle endurance, or physical performance. It has been observed that the drug can modulate endocrine responses to exercise, reducing the acute increase in dihydrotestosterone (DHT) and altering the activation of the hypothalamic-pituitary-adrenal (HPA) axis. Furthermore, increases in markers of oxidative stress and muscle damage have been reported. Thus, although it presents physiological potential, there is no robust evidence to support its ergogenic use, and its consumption without medical indication may represent metabolic and hormonal risks. [resumo fornecido pelo autor]
A tadalafila é um inibidor seletivo da fosfodiesterase tipo 5 (PDE5), indicada para o tratamento da disfunção erétil e da hipertensão arterial pulmonar. Devido à sua ação vasodilatadora, tem despertado interesse no meio esportivo pelo possível efeito ergogênico. No entanto, há escassez na literatura sobre os mecanismos fisiológicos envolvidos no uso dessa substância e seu impacto no desempenho físico. Este estudo, por meio de revisão de literatura, analisou os aspectos farmacológicos e toxicológicos dessa associação. A busca bibliográfica foi realizada na base de dados United States National Library of Medicine (PubMed), utilizando Mesh Terms como booleanos na língua inglesa: (Tadalafil) AND (physical activity OR exercise OR sports performance). Após a aplicação dos critérios de exclusão, foram selecionados nove artigos. Os resultados indicaram que, em indivíduos saudáveis e atletas, a tadalafila não promoveu melhorias significativas no consumo de oxigênio, resistência muscular ou desempenho físico. Observou-se que o fármaco pode modular respostas endócrinas ao exercício, reduzindo o aumento agudo da di-hidrotestosterona (DHT) e alterando a ativação do eixo hipotálamo-hipófise-adrenal (HHA). Além disso, foram relatados aumentos em marcadores de estresse oxidativo e dano muscular. Assim, embora apresente potencial fisiológico, não há evidências robustas que sustentem seu uso ergogênico, e seu consumo sem indicação médica pode representar riscos metabólicos e hormonais. [resumo fornecido pelo autor]
Keywords: Tadalafila; Inibidores enzimáticos; Inibidores da fosfodiesterase 5; Exercícios físicos